General Formalism of the Modified Atomic Orbital Theory for the Rydberg Series of Atoms and Ions: Application to the Photoionization of $Ne^+$ (Journal of Atomic and Molecular Sciences, 2014)
The general formalism of the Modified orbital atomic theory (MAOT) for the Rydberg series of atoms and ions is presented. Energy resonances of the $2s^22p^4(^1D_2)ns,$ $nd,$ $2s^22p^4(^1S_0)ns,$ $nd$ and $2s^2p^5(^3P_2)np$ Rydberg series originating from the $2s^22p^{5}$ $^2P_{1/2}$ metastable and from the $2s^22p^{5}$ $^2P_{3/2}$ ground state of $Ne^+$ are tabulate applying the MAOT formalism. Analysis of the present results is achieved in the framework of the standard quantum defect expansion formula. Comparison is done with the existing experimental and theoretical data.